The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/s18061817
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Embedded Internet of Things Input Shaping Control for Overhead Cranes Transporting Multibody Payloads

Abstract: Input shaping is an Optimal Control feedforward strategy whose ability to define how and when a flexible dynamical system defined by Ordinary Differential Equations (ODEs) and computer controlled would move into its operative space, without command induced unwanted dynamics, has been exhaustively demonstrated. This work examines the issue of Embedded Internet of Things (IoT) Input Shaping with regard to real time control of multibody oscillatory systems whose dynamics are better described by differential algeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Since transient oscillations can be dangerous to both the surroundings and the payload itself, an effective dampening of oscillations has become a focus of research. Effective positioning, as well as residual oscillations, decrease the time spent on loading and unloading [ 1 ]. As an underactuated mechanical system, the sway cannot be arbitrarily controlled, requiring a need for the development of effective control strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since transient oscillations can be dangerous to both the surroundings and the payload itself, an effective dampening of oscillations has become a focus of research. Effective positioning, as well as residual oscillations, decrease the time spent on loading and unloading [ 1 ]. As an underactuated mechanical system, the sway cannot be arbitrarily controlled, requiring a need for the development of effective control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review of various methods for crane dynamic modeling and control reported in the literature up to 2001 is presented in [ 2 ], while more current, state-of-the-art methods (up to 2016) are discussed in [ 3 ]; however, most of the presented approaches are derived from the Euler–Lagrange equation. Other methods that have been applied to modeling material handling systems include Takagi–Sugeno fuzzy models [ 4 , 5 ], bond graph methods [ 6 ], multi-body dynamics [ 1 , 7 ] and neural networks [ 8 ]. Evolutionary algorithms have been implemented in a variety of crane applications including anti-sway crane control [ 9 ], scheduling [ 10 , 11 ] and proactive maintenance [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Representative methods of open-loop control include optimal control [1], [2], trajectory planning [3], [4] and input shaping control [5], [6], yet whose strong dependence and low robustness hinder their application in real-world practices. For this reason, a series of closed-loop control methods have been suggested by numerous scholars, including dynamic PID control [7], fuzzy PID control [8], adaptive neural network control [9], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Various control techniques for overhead cranes are proposed, and they are categorized into open-loop control and closed-loop control according to whether feedbacks are integrated. Open-loop control techniques for overhead crane includes path planning, 810 input shaping, 11,12 filters, 13 etc. The main drawback of these open-loop techniques is that they cannot cope with various external disturbances that exist in the actual operational environment.…”
Section: Introductionmentioning
confidence: 99%